Negotiating Comprehension: Surakarta Elementary Teachers' Perspectives on Reading Pedagogy in the Age of AI - Maulida, Nimas Ayu Nawal; Muamaroh, M; Ratih, Koesoemo; Hikmat, Mauly Halwat (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This qualitative study explores how elementary English teachers negotiate their understanding and practice of reading pedagogy in an era where artificial intelligence tools can instantaneously summarize, analyze, and interpret complex texts. Drawing on reader-response theory and postmodern pedagogical frameworks, this research examines the tensions between traditional notions of "deep reading" and AI-mediated comprehension practices. Through semi-structured interviews with twelve English teachers from diverse school contexts, this study investigates how educators conceptualize authentic comprehension, critical literacy, and the role of intellectual struggle in reading development when students have access to AI assistance. The findings reveal significant concerns about the erosion of effortful reading practices, the shift from personal interpretation to AI verification, and the complex negotiation between accessibility and intellectual growth. Using the pedagogical narrative of Freedom Writers (2007) as a conceptual anchor, this study argues that while AI tools may democratize access to difficult texts, they simultaneously threaten the transformative, meaning-making processes that have long been central to reading education. This research contributes to ongoing debates about literacy education in digital contexts and offers implications for reimagining reading pedagogy that acknowledges both the affordances and limitations of AI technologies. This study particularly focuses on elementary school teachers in Surakarta, Indonesia, as they navigate how to integrate AI technology in early reading instruction while maintaining authentic comprehension and character-based literacy learning.